THE IMPORTANCE OF TRANSPARENCY IN SCHOLARSHIP MANAGEMENT: ADDRESSING PUBLIC TRUST ISSUES IN ISLAMIC INSTITUTIONS - Nur Khalimah; Ulfa Fitria; Nur Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Scholarships in Islamic educational institutions play a crucial role in supporting access to education and shaping an excellent generation. This study employs a literature review approach. However, a lack of transparency in management, such as insufficient financial reporting and unclear selection processes, reduces public trust. This issue can decrease donor participation, open opportunities for unethical practices, and hinder program effectiveness. The findings propose solutions, including detailed financial reporting, independent audits, the use of digital technologies like blockchain, and fostering a culture of transparency. This study emphasizes the importance of transparency as a key to enhancing public trust, upholding accountability, and ensuring the sustainability of scholarship programs in line with Islamic principles. Keywords:Transparency,Scholarship Management, Public Trust, Islamic Institutions